A scoping review of school-based oral health interventions among adolescents in Nigeria - Chukwuemeka, Abel Nnamdi; Oveh, Richard; Dabar, Anita; Afolabi, Omorinola; Ibraheem, Saheed Ademola; Akinsolu, Folahanmi Tomiwa; Salako, Abideen Olurotimi; Alade, Omolola Titilayo; Owotade, Foluso; Eleje, George Uchenna; Ezechi, Oliver; Lusher, Joanne; et al. (Frontiers in Oral Health, 2025)
BackgroundThis scoping review aimed to map school-based oral health interventions for adolescents in Nigeria and to identify gaps that can be addressed to promote optimal oral health in the population.MethodsThis scoping review is registered with the Open Science Framework (OSF) Registries (https://doi.org/10.17605/OSF.IO/CMRV4). An electronic search of PubMed, Scopus, Web of Science, African Journals Online, and Google Scholar for papers focused on oral health interventions implemented in schools in Nigeria, involving adolescents, and published in English between January 2000 and July 2024 was retrieved. Information extracted included study characteristics (author, year, study design), study population characteristics, type of interventions, focus, and key findings.ResultsThe search yielded 392 results, with five studies meeting the eligibility criteria. All studies focused on oral health education, and education was delivered verbally. Four studies assessed the effect of education on oral hygiene practices, three assessed the effect on the consumption of refined carbohydrates, two measured dental service utilization as an outcome, and one assessed smoking cessation. One study showed that peer- and teacher-led models demonstrated comparable effectiveness, making them viable in resource-limited settings.ConclusionThis scoping review found that school-based oral health interventions effectively improved oral hygiene among adolescent populations in Nigeria, though the few studies skewed to southern Nigeria make it difficult to generalize findings to Nigeria. Review registrationOSF, https://doi.org/10.17605/OSF.IO/CMRV4.